2015
DOI: 10.1016/j.jeurceramsoc.2015.08.028
|View full text |Cite
|
Sign up to set email alerts
|

2H-SiC films grown by laser chemical vapor deposition

Abstract: a b s t r a c tWe demonstrated the synthesis of 2H-SiC films on graphite and (0001) sapphire substrates by laser chemical vapor deposition. A tris(dimethylamino) silane was used as a novel precursor for the synthesis of SiC films in a CH 4 atmosphere. The 2H-SiC films were obtained at a deposition temperature of 920 K on the sapphire substrate. The films comprised a-axis-oriented columnar grains and their in-plane orientation relationship was [1000] 2H-SiC // [0001] sapphire and [0001] 2H-SiC // [1000] sapphir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Experimental work by Zangvil & Ruh (1988) found that AlN forms a solid solution with 2H SiC, and their diffusion couple experiments showed that AlN abundances are greater in 2H SiC compared with adjacent 4H SiC (their Table 1). These data imply that Al and N solubilities are likely greater in 2H than 4H; there is limited data on the solubility limit of Al and N in 2H, but the solubility limits of Al and N in 4H are 10 20 cm -3 and 10 19 -10 20 cm -3 , respectively (Linnarsson et al 2003;Ito et al 2015). Although presolar SiC grains with higher order polytypes are rare, they provide information on unique formation conditions in circumstellar environments.…”
Section: Polytypesmentioning
confidence: 99%
“…Experimental work by Zangvil & Ruh (1988) found that AlN forms a solid solution with 2H SiC, and their diffusion couple experiments showed that AlN abundances are greater in 2H SiC compared with adjacent 4H SiC (their Table 1). These data imply that Al and N solubilities are likely greater in 2H than 4H; there is limited data on the solubility limit of Al and N in 2H, but the solubility limits of Al and N in 4H are 10 20 cm -3 and 10 19 -10 20 cm -3 , respectively (Linnarsson et al 2003;Ito et al 2015). Although presolar SiC grains with higher order polytypes are rare, they provide information on unique formation conditions in circumstellar environments.…”
Section: Polytypesmentioning
confidence: 99%
“…Polytypes in SiC are formed when there are differences formed in crystallographic. More than 200 polytypes [13] or 250 polytypes in some reports claimed have been identified but only a few studied on them. Major polytypes of SiC are α-SiC and β-SiC, which are classified as hexagonal polytypes and cubical polytypes respectively.…”
Section: Silicon Carbidementioning
confidence: 99%
“…On the other hand, in electronic properties and application, it is well known as a wide band gap material. 2H-SiC possessed the largest band gap among them compared to other polytypes like 3C-SiC, 4H-SiC, and 6H-SiC [3], [8], [12], [13], [17]. The simulation prediction done by Monte Carlo showed higher electron mobility in 2H-SiC than other polytypes [25].…”
Section: Silicon Carbide Properties and Applicationsmentioning
confidence: 99%
“…Silicon carbide (SiC) is widely used in modern industries such as electronics and reinforcement for composites, due to its good thermal, mechanical, and electronic properties. , Some of their properties, such as the thermal expansivity, elastic constants, hardness, and band gap, depend largely on their polytypes. SiC polytypes are defined by the stacking order of the Si–C bilayer, and over 250 polytypes have been reported. Among these polytypes, β-SiC or 3C-SiC, the only polytype with a cubic structure, and α-SiC or n H-SiC ( n = 4, 6) with a hexagonal structure are the most common and important ones.…”
Section: Introductionmentioning
confidence: 99%